Vulnerable Young People and Their Experience of Online Risks. (4th July 2018) - El Asam, Aiman; Katz, Adrienne
Abstract : While the majority of young people are relatively resilient online, a vulnerable minority report an online life in which they are at risk of multiple harms. With the assumption that vulnerable young people are likely to experience online risks differently, this study examines whether or not being vulnerable offline predicts high risk online experiences (HROEs). Offline vulnerabilities were grouped as Family, Physical, SEN, Communication and Mental Health difficulties, while HROEs were categorized as risks associated with Content, Conduct, Contact, and Cyberscams (4Cs). Using a sample of 2988 young people (aged 10–16 years), multiple linear regression showed that being vulnerable in any group significantly predicted a higher overall score for HROEs. Additionally, statistical analysis showed that individually each of the 4Cs can be explained by different vulnerabilities. Furthermore, experiencing one of the high risk categories predicted the experience of certain other risk categories. The results are explained with reference to previous research and this study sends a strong message for practice: offline vulnerability extends to online life and enhanced, targeted online safety education and support is required.